2022
DOI: 10.3389/fpsyt.2022.923757
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sleep problem in children aged 1–3 years with autism spectrum disorder in Zhejiang province, China

Abstract: BackgroundHigh prevalence of sleep problems have been founded in children with Autism Spectrum Disorder (ASD), with rates ranging from 50 to 80%. We aimed to study the sleep status and the occurrence of sleep problems in children with autism spectrum disorder (ASD) aged 1–3 years, and to provide reference for guiding early comprehensive intervention for ASD children from the perspective of sleep.MethodsFrom January 1 to December 31, 2021, 74 ASD children who met the diagnostic criteria of “Diagnostic and Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on data collected since the COVID-19 pandemic (Table 1). Notably, the research design of all 46 studies was observational: 41 were cross-sectional and 5 were longitudinal . Accordingly, the overall research quality of these studies was determined to be relatively low (according to the GRADE approach) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations